The relationship between exclusive breastfeeding and infant development: A 6- and 12-month follow-up study - Choi, Hye Jeong; Kang, Su Kyoung; Chung, Mi Ra (Early human development, 2018)
Breastfeeding offers several advantages for infants with research suggesting that it benefits development, including cognitive and language development. However, limited research has examined the benefits in infants under one year. To investigate the association between breastfeeding duration and infant development. A longitudinal study conducted over 12 months. Two hundred fifty-five mothers and their infants living in South Korea were seen at three time-points based on infants' age (4, 6, and 12 months). Breastfeeding data were collected at 4 and 6 months. The Korea-Developmental Screening Test for Infants & Children was administered at 6 and 12 months to measure developmental milestones. We analyzed the relationship between breastfeeding duration in the first 6 months and infant development at 6 and 12 months using logistic regression analysis. Compared to infants who did not breastfeed at all, infants who were exclusively breastfed until 4 months of age followed by mixed breastfeeding had a better communication and social interaction at 6 months, and better cognition, communication, and social interaction at 12 months. Exclusive breastfeeding until 6 months of age had no apparent impact on the outcomes at 6 and 12 months. Exclusive breastfeeding up to 4 months of age followed by mixed breastfeeding might maximize the effects of infant development in their first year after birth. Breastfeeding programs should effectively communicate that exclusive breastfeeding for at least 4 months benefits infant development. •Exclusive breastfeeding up to 4 months benefitted infant development.•Communicative and social development improved at 6 months of age.•Cognitive development showed an improvement at 12 months.•Exclusive breastfeeding up to 6 months did not benefit infant development.